(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
This article investigates the role of cultural adaptation in translating advertising texts from English into Uzbek. Advertising discourse is characterized by its persuasive function, emotional appeal, and cultural embeddedness, making word-for-word translation insufficient and often counterproductive. The study examines how cultural values, linguistic structures, and consumer psychology differ between English-speaking and Uzbek-speaking audiences, and how these differences necessitate adaptive translation strategies. Drawing on a corpus of international brand slogans and advertising campaigns localized for the Uzbek market, the article demonstrates that successful advertising translation requires transcreation, cultural substitution, and pragmatic adaptation rather than formal equivalence. The findings suggest that culturally adapted translations are significantly more effective in achieving the intended persuasive impact on Uzbek consumers. The study contributes to the growing body of research on localization and transcreation in translation studies, with particular emphasis on the English-Uzbek language pair.